Sentinel Trees as a Tool to Forecast Invasions of Alien Plant Pathogens - Vettraino, AnnaMaria; Roques, Alain; Yart, Annie; Fan, Jian-ting; Sun, Jiang-hua; Vannini, Andrea (PloS one, 2015)
Recent disease outbreaks caused by alien invasive pathogens into European forests posed a serious threat to forest sustainability with relevant environmental and economic effects. Many of the alien tree pathogens recently introduced into Europe were not previously included on any quarantine lists, thus they were not subject to phytosanitary inspections. The identification and description of alien fungi potentially pathogenic to native European flora before their introduction in Europe, is a paramount need in order to limit the risk of invasion and the impact to forest ecosystems. To determine the potential invasive fungi, a sentinel trees plot was established in Fuyang, China, using healthy seedlings of European tree species including Quercus petreae, Q. suber, and Q. ilex. The fungal assemblage associated with symptomatic specimens was studied using the tag-encoded 454 pyrosequencing of the nuclear ribosomal internal transcribed spacer-1 (ITS 1). Taxa with probable Asiatic origin were identified and included plant pathogenic genera. These results indicate that sentinel plants may be a strategic tool to improve the prevention of bioinvasions.